2017
DOI: 10.24295/cpsstpea.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Research and Applications of Switched Reluctance Drives

Abstract: Abstract-Electrical drives are one of the major consumers of electrical energy and their penetration in the market is still growing. Hence, for many drive applications efficient, reliable and cost effective solutions have to be found. Switched reluctance drives (SRD) offer a potential solution when focus is mainly on cost and robustness. However, to benefit from the unique advantages of this machine type a deep understanding of its strongly non-linear behavior is required. After discussing some major differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…In the machine design the main challenge and limiting factor is thermal constrain due to winding on stator and rotor [13]. There is a great interest in machines with reduce mass of magnet or having no magnet, in general for current technologies the switched reluctance machines have pushed the boundaries for traction motor drives applications due to simple and robust construction, absence of demagnetization, no copper winding on the rotor with the main focus on cost, robustness and high temperature environment applications [14]. The main advantage of SRM is a very extensive field weakening area, up to 10 time has been appealed.…”
Section: Motor Drives For Evmentioning
confidence: 99%
See 1 more Smart Citation
“…In the machine design the main challenge and limiting factor is thermal constrain due to winding on stator and rotor [13]. There is a great interest in machines with reduce mass of magnet or having no magnet, in general for current technologies the switched reluctance machines have pushed the boundaries for traction motor drives applications due to simple and robust construction, absence of demagnetization, no copper winding on the rotor with the main focus on cost, robustness and high temperature environment applications [14]. The main advantage of SRM is a very extensive field weakening area, up to 10 time has been appealed.…”
Section: Motor Drives For Evmentioning
confidence: 99%
“…In order to meet the demand, now a days there is more attention in the low cost switched reluctance motor drive system because of several advantage such as robust construction, normally cheap, design simplicity, no winding on rotor and absence of demagnetization which is the most suitable for electric and hybrid electric vehicle [14,22,[26][27][28][29][30].…”
Section: Motor Drives For Evmentioning
confidence: 99%
“…Analytical models and lookup tables are much faster but have reduced accuracy. Therefore, SRM modeling must be addressed as a trade-off between simulation accuracy and computational speed [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that improving the SRM control strategy is a more cost-effective way to deal with the SRM noise and torque ripple. The main aspects of machine modeling, design and control are very well presented in Burkhart et al (2017). The most appreciated advantage of this motor is the non-use of neither rare elements nor windings on the rotor.…”
Section: Introductionmentioning
confidence: 99%